Relationship between knowledge, understanding and behavior of committing offenses under the computer-related offenses of informal workers in Nakhon Sawan Province - khamsai, supaporn; Prasomtong, Nawaporn (NIDA Business Journal, 2023)
The study examined 1. The level of knowledge and understanding of the Computer Crimes Act of informal workers in Nakhon Sawan province, 2. The behavior regarding the Act, and 3. The relationship between knowledge and offender behavior. The sample of this study included 400 informal workers. The questionnaire collected data using test hypotheisis significant .05 and using by descriptive statistics proportion with Mean, Standard Deviation, and Test hypothesis with Independent t-test, F-test and Pearson’s Product Moment Correlation. The findings were as follows: Most respondents were male, 40-44 years, and college-educated. Downloading and uploading data took over 4 hours. When considering each aspect, it was found that: 1) Knowledge and understanding: most respondents were well-informed. 2) According to the Computer Crimes Act in Nakhon Sawan province, most informal workers behaved at the never level. 3) Knowledge and understanding of the Computer Crimes Act affected offense behavior with an inverse relationship. If informal workers in Nakhon Sawan province had high knowledge and understanding, they would be less guilty, which was the opposite relationship.